Impact of premature coronary artery disease on adverse event risk following first percutaneous coronary intervention - Pinxterhuis, Tineke H.; Ploumen, Eline H.; Zocca, Paolo; Doggen, Carine J. M.; Schotborgh, Carl E.; Anthonio, Rutger L.; Roguin, Ariel; Danse, Peter W.; Benit, Edouard; Aminian, Adel; Hartmann, Marc; Linssen, Gerard C. M.; et al. (Frontiers in Cardiovascular Medicine, 2023)
Objectives We assessed differences in risk profile and 3-year outcome between patients undergoing percutaneous coronary intervention (PCI) for premature and non-premature coronary artery disease (CAD). Background The prevalence of CAD increases with age, yet some individuals develop obstructive CAD at younger age. Methods Among participants in four randomized all-comers PCI trials, without previous coronary revascularization or myocardial infarction (MI), we compared patients with premature (men <50 years; women <55 years) and non-premature CAD. Various clinical endpoints were assessed, including multivariate analyses. Results Of 6,171 patients, 887(14.4%) suffered from premature CAD. These patients had fewer risk factors than patients with non-premature CAD, but were more often smokers (60.7% vs. 26.4%) and overweight (76.2% vs. 69.8%). In addition, premature CAD patients presented more often with ST-segment elevation MI and underwent less often treatment of multiple vessels, and calcified or bifurcated lesions. Furthermore, premature CAD patients had a lower all-cause mortality risk (adj.HR:0.23, 95%-CI: 0.10–0.52; p < 0.001), but target vessel revascularization (adj.HR:1.63, 95%-CI: 1.18–2.26; p = 0.003) and definite stent thrombosis risks (adj.HR:2.24, 95%-CI: 1.06–4.72; p = 0.034) were higher. MACE rates showed no statistically significant difference (6.6% vs. 9.4%; adj.HR:0.86, 95%-CI: 0.65–1.16; p = 0.33). Conclusions About one out of seven PCI patients was treated for premature CAD. These patients had less complex risk profiles than patients with non-premature CAD; yet, their risk of repeated revascularization and stent thrombosis was higher. As lifetime event risk of patients with premature CAD is known to be particularly high, further efforts should be made to improve modifiable risk factors such as smoking and overweight. Clinical Trial Registration [clinicaltrials.gov], TWENTE [NCT01066650]; DUTCH PEERS [NCT01331707]; BIO-RESORT [NCT01674803]; BIONYX [NCT02508714].